Molecules that changed the world : a brief history of the art and science of synthesis and its impact on society - Nicolaou, K. C. 4 0 16; (Tamsyn) Montagnon, T.; 5 (Weinheim [Germany] : Wiley-VCH, 2008)
Presents an illustrated introduction to the world's most important molecules and the scientists who discovered or developed them, revealing how certain compounds, such as camphor, penicillin, and morphine, have influenced the fields of drugs, aromatics, or vitamins.
Includes bibliographical references and indexes.
Science Books & Films (A.A.A.S.)
Adult;Adult
Keywords: 2 -- 0; 6; Synthesis.;Synthesis. -- Organic compounds;Organic compounds; 20; 2